Endoscopic and Microsurgical Approaches to the Cavernous Sinus – Anatomical Review - Romero, Flavio Ramalho; Ramires, Daphyne; Cristiano, Luigi Carrara; Silva, Marcos Paulo; Vieira, Rodolfo Brum (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Cavernous sinus surgery has always represented a surgical challenge due to the great importance of the surrounding anatomical structures and to the high morbidity associated to it. Although the anatomy of this region has been extensively described, controversy remains related to the best treatment and approaches for different kinds of lesions. In this article, a literature review was performed on the surgical anatomy and approaches to the cavernous sinus.
Keywords: cavernous sinus; endoscopic endonasal approach; transsphenoidal surgery; transpterygoid approach; microsurgical cavernous sinus